Emphaty, humanization and connection.: Brand communication in the pandemic. - Valença da Silva, Lívia (2021)
The market and the communications industry have been suffering a lot from the impacts of the new coronavirus. The pandemic period has been an opportunity for brands to make a new communication, demonstrating much more commitment to people and society. One of the great challenges has been to shift the focus from sales to direct actions with more purpose, empathy and responsibility, considering that thousands of lives are at risk and the economy has entered a sharp recession, with drastic consequences for a country already well marked by social inequality. This is the time for brands to be more useful to society and that is why they are being charged: legitimate purposes and relationships with deeper consumers, treating them, in fact, as more active, engaged and connected human beings. But how are brands actually acting? You need to be firm and focus on empathic and holistic communication.